In situ isolation of haloalkaliphilic microalga from the Yellow River Delta: enhancing legume crop resilience under saline-alkali stresses - Xiaoli Zhu; Minmin Xu; Jiahao Liang; Shenkun Liu; Xiao Yu; Yanpeng Pan; Guangwen Zhu; Xiaojing Wang; Jianchao Yang; Kang Wang; ZhiHai Zhong; Chenggang Ren; et al. (Algae, 2025)
Coastal saline-alkaline soils in China's Yellow River Delta represent vital yet underutilized arable reserves, where crop productivity is severely constrained by dynamic salinity-alkalinity stress, compounded by the scarcity of native stress-adapted biological resources for sustainable remediation. This study addressed this critical gap through in situ isolation of a novel halo-alkaliphilic microalga from saline waters, identified as Desmodesmus sp. R1108 via morphological characterization (distinctive single/quad-cell palisade structures; 8 × 4–6 μm cells) and molecular phylogeny. The strain exhibited unprecedented alkaliphilic traits, demonstrating 35% enhanced growth at 100 mM NaHCO3 while tolerating pH 10.0. Crucially, soil irrigation with live cells significantly boosted Sesbania cannabina resilience across multiple stress regimes: germination rates surged 47% under 200 mM NaCl, plant height increased 42% under 200 mM NaHCO3 , and root biomass rose 56% under neutral salt stress—representing a novel application of a locally isolated, halo-alkaliphilic microalga via soil irrigation to leverage intrinsic stress-adaptation mechanisms for green-manure legume cultivation. This pot-scale study demonstrates a promising, eco-friendly bioinoculant approach that enhanced legume growth by 27–47% under controlled saline-alkaline conditions, highlighting its potential as a foundational strategy for the future development of scalable remediation techniques for marginal saline ecosystems.